Neutrophil Lymphocyte Ratio as A Predictor of The First Onset Acute Neutropenia After R-CHOP Chemotherapy in Diffuse Large B-cell Lymphoma Patients - Christine, Griskalia; Sukrisman, Lugyanti; Sutandyo, Noorwati; Rumende, Cleopas Martin (UI Scholars Hub, 2019)
Background. Diffuse Large B-cell Lymphoma (DLBCL) is the most common lymphoma in Indonesia. R-CHOP chemotherapy has a moderate risk for neutropenia / febrile neutropenia. Lymphocytes can describe host immunity, while neutrophils and monocytes can describe the inflammatory response. No study has assessed differential count of leukocytes as a predictor of the first onset acute neutropenia after R-CHOP chemotherapy in DLBCL patients. This study aimed to determine the relationship between differential count of leukocytes before chemotherapy as a predictor of the first onset acute neutropenia after R-CHOP chemotherapy in DLBCL patients. Methods. A retrospective cohort study was conducted among 18–60 years old DLBCL patients with ECOG 0–1 and no comorbidity related to chemotherapy 18–60 years old. Subjects were given with the first 3 cycles of R-CHOP chemotherapy without G-CSF prophylaxis. Results. Of the 95 patients, first onset acute neutropenia after chemotherapy occurred in 83 (87.4%) subjects or 83 (55.3%) cycles of 150 chemotherapy cycles. Febrile neutropenia occurs in 50.6% of the onset of neutropenia. Severe neutropenia occurs in 34 (41.0%) cycles of 83 neutropenic episodes. The first onset of acute neutropenia was the most common at 7–15 days after chemotherapy. The AUC of neutrophil lymphocyte ratio was 0.74 (95% CI 0.65–0.82); while absolute lymphocytes, absolute neutrophils, absolute monocytes, and monocyte lymphocyte ratios were 4.1 neutrophil lymphocyte ratio were able to predict the first onset of acute neutropenia after RCHOP chemotherapy in DLBCL patients (sensitivity 71.1%; specificity 64.2%; positive predictive value 71.1%; negative predictive value 64.2%). Conclusion. Neutrophil lymphocyte ratio before chemotherapy > 4.1 is a predictor of the first onset acute neutropenia after R-CHOP chemotherapy in DLBCL patients.